Glaucoma in a case of Hurler disease. Issue 10 (October 1980) - Spellacy, E; Bankes, J L; Crow, J; Dourmashkin, R; Shah, D; Watts, R W
Abstract : The electron microscopic appearances of the corneoscleral and iris tissue removed at operation from a child with Hurler disease and glaucoma showed distinctive swollen cells with intracellular inclusions similar to those which are observed in other tissues in these patients and which are due to abnormal lysosomal storages of mucopolysaccharides. Some recent observations on the possible relationship between mucopolysaccharides and the drainage of fluid from the anterior chamber are briefly reviewed and correlated with the present observations. The development of glaucoma in this patient is thought to be associated with the presence of the mucopolysaccharide-containing cells in the region of the aqueous drainage channels.